The reformational philosophy re-formed: Daniël Strauss’s major contribution toward invigorating the Philosophy of the Cosmonomic Idea - Cameron, Alan (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2011)
Philosophy: Discipline of the Disciplines (Philosophy) is arguably the most important work to date by the leading reformational philosopher, D.F.M. Strauss. This is a review article that discusses what this author considers to be amongst the most significant innovations and developments in the Philosophy of the Cosmonomic Idea (PCI) since the first publication of Herman Dooyeweerd’s A New Critique of Theoretical Thought. The article will indicate how these developments by Strauss, brought together in Philosophy, have contributed towards realizing Dooyeweerd’s wish to see scholars within their own specialist fields working in a self-critical and collegial manner out of a Christian perspective that does justice to the richness, diversity and potential for the unfolding of God’s Creation. It concludes with an interdisciplinary example of the application of the revised PCI philosophy, and one of Philosophy’s novel conceptual insights, in particular, toward deepening the understanding of a sphere of professional educational practice to which the author of this article belongs.